2008
DOI: 10.1103/physreve.78.026706
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulation of nonequilibrium effects in oscillatory gas flow

Abstract: This version is available at https://strathprints.strath.ac.uk/7303/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…The phase lag and amplitude reduction are a result of the increase in slip. Tang et al [29] also observed similar phase lag of fluid velocity for different Stokes numbers and TMAC in their Lattice Boltzmann simulation of oscillatory gas flows.…”
Section: Phase Lag Of Fluid Velocity Due To Wall Hydrophobicitymentioning
confidence: 59%
See 1 more Smart Citation
“…The phase lag and amplitude reduction are a result of the increase in slip. Tang et al [29] also observed similar phase lag of fluid velocity for different Stokes numbers and TMAC in their Lattice Boltzmann simulation of oscillatory gas flows.…”
Section: Phase Lag Of Fluid Velocity Due To Wall Hydrophobicitymentioning
confidence: 59%
“…Boundary slip has been the subject of less investigation in unsteady flows. A few exceptions are in unsteady gas flows [26,27] and analytic solutions for continuum scale problems [28][29][30][31]. However, to the authors knowledge, for liquids at micro-scales the research has been limited to steady flows.…”
Section: Introductionmentioning
confidence: 99%
“…While several canonical shear-driven gas flows, e.g, oscillatory Couette flow, have been examined using a variety of numerical and analytical methods, these flows are isothermal in the linear limit (Park, Bahukudumbi & Beskok 2004;Hadjiconstantinou 2005a;Sharipov & Kalempa 2007Tang et al 2008). The leading-order effect of unsteadiness in these flows occurs via a modification to the classical Navier-Stokes description at second order in the Knudsen number, i.e.…”
Section: J Nassios and J E Sadermentioning
confidence: 99%
“…In the pressure-driven flow, this "wall-scaling" approach provides a significant improvement for Knudsen numbers up to 0.5. Later, this scheme has also been applied to study the rarefied thermal [31] and oscillatory Couette flow [32] in the early transition flow regime with great success.…”
Section: Introductionmentioning
confidence: 99%